(untitled) (Journal of Economic Research & Business Administration, 2016)
As international experience shows the development of the tourism sector of the economy is a source of economic development. But the industry is, in turn, requires a set of measures for development. These include transport, infrastructure, trade, health, etc. In turn, from vyssheskazannogo special attention must be paid to transport infrastructure. The rapid development of the economy promotes the growth of large-scale industrialization and modernization of foreign economic relations of production, transport and logistics capabilities. Taking into account the unique geographical position of our country, as well as the convenience of major transport routes in Eurasia, Kazakhstan has to take the initiative on the creation of a large transit hub. The country is located in the center of the Eurasian continent with great transit potential of the large volume of freight traffic, and sootvntstvenno should be integrated into the international transport system. In order to enter into the international economic system began construction of the road, naming the Great Silk Road of XXI century «Western Europe - Western China».